Minimum Wage in Germany: Countering the Wage and Employment Gap between Migrants and Natives? - Kai Ingwersen; Stephan L. Thomsen (Institute of Labor Economics (IZA), 2022)
This paper investigates the effects of the introduction of a statutory minimum wage in Germany on the wages and employment of migrants. Migrants are an overrepresented group in the low-wage sector and can be expected to particularly benefit from a minimum wage. We combine a "differential trend adjusted difference-in-differences estimator" (DTADD) and descriptive evidence to evaluate the impact of the minimum wage introduction in 2015 on hourly wages, monthly salaries, working hours and changes in employment and wage distribution. Contrary to expectations, our results show that the introduction of the minimum wage has weakened the position of migrants in the low-wage sector compared to their native counterparts. We observe an increase in part-time employment, a less pronounced decline in unemployment and a greater reduction in weekly working hours among migrants. The introduction of the minimum wage caused a temporary convergence in hourly wages between migrants and natives, which subsequently turned into a wage divergence. Migrant men in the low-wage sector have been particularly negatively affected by the introduction of the minimum wage. Moreover, increasing hourly wages have not translated into higher monthly salaries, thus widening wage inequality between migrants and natives.
Keywords: J31; J63; J38; J21; 330; minimum wage; migrants; differential trend adjusted difference-in-differences; SOEP